Pest categorisation of Phymatotrichopsis omnivora - Bragard, Claude (John Wiley and Sons Inc., 2019)

(untitled) (EFSA J)
The Panel on Plant Health performed a pest categorisation of Phymatotrichopsis omnivora, the causal agent of Phymatotrichum root rot of more than 2,000 dicotyledonous plant species, for the EU. The pest is listed as Trechispora brinkmannii in Annex IAI of Directive 2000/29/EC. P. omnivora is a well‐defined fungal species and reliable methods exist for its detection and identification. It is present in south‐western USA, northern Mexico, Libya and Venezuela. The pest is not known to occur in the EU. P. omnivora has an extremely wide host range; quantitative impacts have been documented for Gossypium spp. (cotton), Medicago sativa (alfalfa), Malus domestica (apple), Prunus persica (peach) and Vitis vinifera (grapevine) as the major cultivated hosts. All major hosts and pathways of entry of the pest into the EU are currently regulated, except for soil and growing media attached or associated with plants originating in Libya. Host availability and climate and edaphic matching suggest that P. omnivora could establish in parts of the EU and further spread mainly by human‐assisted means. The pest infects the roots causing wilting and death of its host plants. The introduction of the pest in the EU territory would potentially cause direct and indirect impacts at least to cotton, alfalfa, apple, peach and grapevine production. The main uncertainties concern the host range, the extrapolation to the EU of the climatic and edaphic conditions favouring the disease in some of the infested areas, the role of conidia in the epidemiology of the disease and the magnitude of potential impacts to the EU. P. omnivora meets all the criteria assessed by EFSA for consideration as potential Union quarantine pest. The criteria for considering P. omnivora as a potential Union regulated non‐quarantine pest are not met, since the pest is not known to occur in the EU.